Cost uniqueness and information uncertainty - Anderson, Mark; Mashruwala, Raj; Wang, Ye; Zhao, Rong (Contemporary Accounting Research, 2023)
Abstract Prior literature has studied firm uniqueness and its implications for capital market participants by investigating earnings uniqueness. We recognize that cost and revenue uniqueness provide separate insights about firm uniqueness because different forces drive firm‐specific revenues and costs. Cost uniqueness is of special interest because costs are opaque to investors and more complex than revenues. Therefore, we examine how cost uniqueness affects information uncertainty from the perspective of external participants. We find that idiosyncratic stock return volatility increases with cost uniqueness independently and incrementally from revenue uniqueness. We validate these results with several cross‐sectional tests that provide insights into the forces that drive the association between information uncertainty and cost uniqueness. In addition, we find that higher cost uniqueness is associated with finer cost disclosure. Overall, we show that cost uniqueness is an important dimension of cost behavior that is linked to strategic decision‐making and affects uncertainty surrounding firm valuation.